Riga-Fede Disease - Ghimire, Neeta; Maharjan, IK; Kumar, A; Koirala, B (Health Renaissance, 2013)
The term Riga-Fede disease has been used historically to describe traumatic ulceration that occurs on the ventral surface of tongue in neonates and infants. The natal and neonatal tooth have been reported to cause ulceration on the ventral surface of the tongue which may affect the child.s feeding habits. This appearance was described by Riga and Fede and hence been termed as Riga-Fede disease. It is important to diagnose the lesion early and treat it by eliminating the cause of trauma to avoid untoward complications. Treatment option can be either conservative or extraction of natal and neonatal tooth. This paper presents a case of Riga-Fede disease resolved by conservative treatment i.e., grinding, after which the infant started feeding normally. Health Renaissance, January-April 2013; Vol. 11 No.1; 174-176 DOI: http://dx.doi.org/10.3126/hren.v11i2.8230